Analysis of Relation Between Impact Strength and Torsional Strength in Palm Fiber-Reinforced Epoxy Resin Composite Materials - Wirawanto, Teguh; Fitri, Muhamad (Universitas Mercu Buana, 2025)
Composites are a combination of matrix or binder materials with reinforcement. The combination will produce a composite material that has different mechanical properties and characteristics from the constituent material, so that a desired composite material can be planned. The abundance of natural resources of palm fiber from palm trees but its utilization is still lacking, due to the mechanical properties of this fiber which is still in doubt about its reliability. For this reason, it is necessary to conduct research on epoxy resin composites with fibers as a filler so that the mechanical properties of each fiber and matrix composition can be known. The study used an experimental method that began with the manufacture of composite materials for the test specimens using an epoxy resin matrix reinforced with fibers with fiber volume fraction variations of 0%, 5%, 7% and 9%. Testing the mechanical properties of composite materials, which in this case is testing the torsional strength and impact strength of composite materials with variations in some fiber content, is then carried out simulations using the test data. The results of this study obtained an optimum average impact strength of 13.00 kJ/m on a composite material with a fiber content of 9% and obtained an optimum torsional strength with an average torque value of 271.14 N.m and an average stress value. shear of 2698.48 MPa on a composite material with a fiber content of 9%. The data obtained shows that the higher the percentage of fiber used, the greater the impact strength and torsional strength produced by the fiber-reinforced composite material.